AB0454 The Outcome of SLE Residents of Kyrgyzstan According To The Prospective Study. (15th July 2016) - Koilubaeva, G.; Aseeva, E.; Soloviev, S.; Nasonov, E.; Reshetnyak, T.; Djumagulova, A.; Eralieva, V.; Karimova, E.
Abstract : Background: Systemic lupus erythematosus (SLE) is a devastating disease affecting different organs, ultimately leading to organ failure and death. To date, there are no data regarding the real-life picture of SLE in Kyrgyzstan. Objectives: To study the outcomes of SLE according prospective study among residents of Kyrgyzstan. Methods: An 2-year prospective analysis of patients with SLE with a specially developed research base (BLIPS 8, ADS-Limathon).60 patients with definite diagnosis of SLE (ACR, 1997; SLICC, 2012), were treated in the department of rheumatology of NCCIM and observed from 2012 to 2015. They were evaluated by sex, age, disease duration, activity of SLE according the SLEDAI-2K, irreversible organ damage by SDI, therapy, with monitoring of all parameters every six months for 2 years. From the data of the immunological studies immune linear (immunoblot) "ANA-LIA-Max 17" were analyzed with a purpose of detecting the antibodies of double-stranded DNA, Sm D1 antigen and antibodies of double-stranded DNA-linked immunosorbent analyisis (ELISA), C3-C4 components complement, indirect immunofluorescence of the antinuclear antibody cells of line Hep-2. Results: The vast majority were women (86.7%), with average age 30 years old, with disease duration of about 1.0 years. Periods to verify the diagnosis ranged from 1 month to 9 years. The clinical course was dominated by patients with acute version (47%) and high activity (57%). In the debut of the disease most common clinical symptoms were cutaneous and articular syndrome (84.2% and 72.3%, respectively), the defeat of the serous membranes (88%) and kidney (68%). The development of irreversible organ damage recorded in half the patients (46%), on average of 6 months from the onset of the disease, preferably with low (36.7%) and the average SDI (21.7%). Among the irreversible organ damage leading place is occupied by respiratory failure (53.5%) of them with pulmonary fibrosis (21.4%) and pulmonary hypertension (25%). Second place takes kidney disease (50%) with severe forms of nephritis (nephrotic syndrome and chronic renal failure). Irreversible changes in the central nervous system were observed in 21% of patients. Over the whole period there were 14 fatal cases (19.4%). They were mostly women (72%) with average age 37.9 years, with disease duration around 4 years. The main causes of death were active SLE and its complications: kidney disease (29%), central nervous system (CNS)-21.4% and combined CNS and lung (21.4%). During the two-year observation, despite the significant decrease in disease activity (p<0, 001), the progression of SDI (p<0, 0001), deterioration of whom are independent from both the activity and the variant of the disease (r =0.18, p=0.2; r =0.03, p=0.8 respectively) is noted. However, the degree of organ damage depended on the duration of illness (r=0.27, p<0, 03) and the age of patients (r =0.29, p=0.02). Conclusions: Irreversible organ damage of the respiratory organs (pulmonary fibrosis, pulmonary hypertension), renal, and CNS were the main predictors of adverse outcome of SLE among the residents of Kyrgyzstan. Disclosure of Interest: None declared